Effect of Hydrogen on the Development of Superplastic Deformation in the Submicrocrystalline Ti–6Al–4V Alloy; Materials Science Forum; Vol. 838-839 - Grabovetskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Ratochka I. V. Iljya Vasiljevich; Mishin I. P. Ivan Petrovich; Zabudchenko O. V. Olga Vyacheslavovna (Microstructure Refinement, 2016)
Title screen